A Analytical Review on Methods for the Isolation and Determination of Glycyrrhizic Acid from Glycyrrhiza glabra - M Khanahmadi (Journal of Medicinal Plants, 2014)
Glycyrrhiza glabra (Licorice) is a perennial shrub belongs to the Fabaceae family. It is widely used in food pharmaceutical products and tobacco industry because of its important secondary metabolites. Due to worldwide uses of licorice, it has significant role in export. One of the main bioactive compounds of the root is glycyrrhizic acid (GA) which is a saponine containing three carboxyl and five hydroxyl groups. Glycyrrhizic acid is used as an anti-inflammatory and anti-allergic remedy for the treatment of bronchial asthma, eczemas and other diseases. There are different methods for separation, purification, and analysis of glycyrrhizic acid (GA) from licorice roots. Most accepted technologies of them include using of solvents, water separation, polymeric macro porous resin and non-ionic surfactants. Also, high-performance liquid chromatography technique is the most important in analysis of GA.